4
$\begingroup$

Where $AB$ is the product of the sets and $A,B \in \mathbb{R^+}$.

Since $A,B$ are bounded above sup $A$ and sup $B$ exist. Let $\alpha = $ sup $A$ and $\beta = $ sup $B$. This implies $\forall a \in A$ and $\forall b \in B$ $a \leq \alpha$ and $b \leq \beta$. Then $ab \leq \alpha\beta$ because $a,b > 0$. Thus $ab$ is bounded above and sup $AB$ exists and sup $AB \leq \alpha\beta$. \ We now show sup $AB \geq \alpha\beta$. \ Let $\varepsilon > 0$ then $\exists a \in A$ s.t. $\alpha - \varepsilon < a \leq \alpha$ and $\exists b \in B$ s.t. $\beta - \varepsilon < b \leq \beta$. So: \begin{equation*} (\alpha-\varepsilon)(\beta-\varepsilon) < ab \leq \alpha\beta \text{ since } a,b,\varepsilon > 0 \end{equation*} \begin{equation*} = \alpha\beta-\varepsilon(\alpha+\beta-\varepsilon) < ab \leq \alpha\beta \end{equation*}

I spoke with my professor today about this and he suggested I show that $\varepsilon$ is sufficiently small to proceed. I'm not sure exactly how to write this detail.

EDIT: I was meant to show what $\varepsilon$ was bounded by to proceed. The proof below realizes this idea. Feedback is welcome and appreciated.

Since $A,B$ are bounded above sup $A$ and sup $B$ exist. Let $\alpha = $ sup $A$ and $\beta = $ sup $B$. This implies $\forall a \in A$ and $\forall b \in B$ $a \leq \alpha$ and $b \leq \beta$. Then $ab \leq \alpha\beta$ because $a,b > 0$. Thus $ab$ is bounded above, sup $AB$ exists and sup $AB \leq \alpha\beta$. Let $\varepsilon > 0$ then $\exists a \in A$ s.t. $\alpha - \varepsilon < a \leq \alpha$ and $\exists b \in B$ s.t. $\beta - \varepsilon < b \leq \beta$. So: \begin{equation*} (\alpha-\varepsilon)(\beta-\varepsilon) < ab \leq \alpha\beta \end{equation*} \begin{equation*} = \alpha\beta-(\varepsilon\alpha+\varepsilon\beta-\varepsilon^2) < ab \leq \alpha\beta \end{equation*} Since $ab$ is bounded above by $\alpha\beta$ we have $ab \leq \text{ sup}(AB)$. We let $\varepsilon' = \varepsilon\alpha+\varepsilon\beta-\varepsilon^2 > 0 $ so $\forall(0 < \varepsilon' < \alpha+\beta)$ we have $\alpha\beta-\varepsilon'< ab < \text{ sup}(AB) \implies \alpha\beta \leq \text{ sup}(AB) + \varepsilon' \implies \alpha\beta \leq \text{ sup}(AB)$ by ``elbow room''.

$\endgroup$
1
$\begingroup$

You are almost there, from the first inequality of your last line $$\alpha\beta- \epsilon (\alpha + \beta - \epsilon) < ab \leq \sup AB$$ Observe that the right hand side $\sup AB$ is independent of $\epsilon$, send $\epsilon$ to zero. Then $$\alpha\beta \leq \sup AB.$$

$\endgroup$
4
  • $\begingroup$ Right I understand that part but don't I need to show the $\epsilon$ is "small enough"? $\endgroup$
    – Chris
    Oct 7 '15 at 2:15
  • 1
    $\begingroup$ @Chris An $\epsilon$-argument works like the following, if for each $\epsilon>0$, we have $$a-\epsilon \leq b$$, then we can conclude $$a\leq b.$$ What do you mean by $\epsilon$ is small enough? $\endgroup$
    – Xiao
    Oct 7 '15 at 2:19
  • $\begingroup$ Right so in this case ϵ(α+β−ϵ) becomes our $\epsilon$. I'm not sure, my professor said I needed to show that it was small enough and that my proof was lacking something. $\endgroup$
    – Chris
    Oct 7 '15 at 2:23
  • $\begingroup$ @Chris I believe the important part here is moving from the term $ab$ to $\sup AB$, because by the way you choose $a$ and $b$, $ab$ depends on $\epsilon$. $\endgroup$
    – Xiao
    Oct 7 '15 at 2:25
1
$\begingroup$

I will try to be as clearly as posible.

For $A, B \subseteq \mathbb{R}^+$, we will prove that $Sup(A)\cdot Sup(B) = Sup(AB)$. For this, we will prove that $Sup(A)\cdot Sup(B) \leqslant Sup(AB)$ and $Sup(AB) \leqslant Sup(A)\cdot Sup(B)$. Of course, $AB=\{xy:x\in A~\wedge~y\in B\}$.

Let, $$a=Sup(A), b=Sup(B), M=Sup(AB)$$

Proof ($Sup(A)\cdot Sup(B) \leqslant Sup(AB)$).

By definition, $\forall x\in A(x\leqslant a)$ and $\forall y\in B(y\leqslant b)$. Since $A, B \subseteq \mathbb{R}^+$, $x, y>0$ thus $0<x\leqslant a$ and $0<y\leqslant b$ where it follows that $xy\leqslant ab$, where $xy\in AB$. This means that $AB\leqslant ab$ which implies that $M\leqslant ab$.

Now, by definition, $\forall z\in AB (z\leqslant M)$. Since $z\in AB$, $z=xy$ where $x\in A$ and $y\in B$ thus $xy\leqslant M$. Since $x, y>0$, $xy>0$, this way we can define the quotient $x\leqslant \frac{M}{y}$ which means that $\frac{M}{y}$ is an upper bound for $A$ which implies that $a\leqslant \frac{M}{y}$. It follows that $ay\leqslant M$ thus $y\leqslant \frac{M}{a}$ which means that $\frac{M}{a}$ is an upper bound for $B$ which implies that $b\leqslant \frac{M}{a}$. Therefore, $ab\leqslant M$.

$$\therefore Sup(A)\cdot Sup(B) = Sup(AB)$$

$\endgroup$
0
$\begingroup$

Proceeding with your argument:

$$\alpha \beta -\varepsilon(\alpha+\beta -\varepsilon)<ab\le \alpha \beta$$

and this is true for every $\varepsilon>0$. Now let $\eta >0$ be arbitrary, and put $\varepsilon = \min \left \{\frac{2\eta}{\alpha+\beta} , \frac{\alpha+\beta}{2}\right \}$. It follows that:

$$\alpha+\beta-\varepsilon\ge\frac{\alpha+\beta}{2}\implies -\varepsilon(\alpha+\beta-\varepsilon)\ge-\varepsilon \left (\frac{\alpha+\beta}{2}\right )$$

Hence:

$$\alpha\beta -\varepsilon \left (\frac{\alpha+\beta}{2}\right )<ab$$

By our choice of $\varepsilon$:

$$\alpha\beta <\varepsilon \left (\frac{\alpha+\beta}{2}\right )+ab \le \eta +ab$$

Since $\eta >0$ is arbitrary, the conclusion follows.

$\endgroup$
1
  • $\begingroup$ Why $\alpha +\beta -\epsilon \geq {\alpha + \beta \over 2} \implies -\epsilon(\alpha + \beta -\epsilon) \geq - \epsilon ({{\alpha + \beta } \over 2})$ ?? you are multiplying by a negative number $- \epsilon$, right? $\endgroup$ Aug 24 '17 at 19:22

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.